General Educator Perceptions of School Support in Teaching Students with an IEP - Kenny, Faith (Journal of the American Academy of Special Education Professionals, 2019)
Historically, researchers have focused on the perceptions of special education teachers regarding inclusion. Research has shown that general education teachers who feel supported by their schools provide better classroom experiences for all students (Hwang and Evans, 2011). This study expanded upon this thinking by asking general educators what they felt were the most beneficial supports in meeting the needs of students with an Individualized Education Plan (IEP). Results indicated that general education teachers viewed their ability to meet the needs of diverse learners positively. Respondents felt they had a positive relationship with special education teachers, even though little collaborative planning time was given Respondents additionally affirmed that smaller class size, more paraprofessional assistance, and more individual planning time were needed. These findings powerfully suggest that general educators value collaborative and individual planning time to meet the needs of their students. Overall, this study provides tangible ways that school administrators can provide desired support to general education teachers.